Mapping of the Hinduism Convertion and The Impact on Hindu Young Generation in Southeast Sulawesi (Case Study of Hinduism to Non-Hinduism) - I Gede Purwana; I Nyoman Sudiana; I Nengah Suliarta; Kadek Seprani (IAHN-TP Palangka Raya, 2019)
The study on the Mapping of the Hinduism Conversion and the Impact on Young Hindu Generation in Southeast Sulawesi (Case Study of Hinduism to Non-Hindus) had been carried out. This study aims to investigate the general description of Hinduism conversion that occurred in southeast Sulawesi and how it impacts on young Hindu generation. The method that used in this study was mixed methods, but it dominates by quantitative analysis methods, while the qualitative forgive the description. The sampling technique used in this study was purposive sampling, while the purposes of data collection used in this study were: observation, interviews, document recording, and predictive surveys. The techniques of data analysis used in this study were interpretation data, reduction, presentation, conclusions, and verification. The results of this study indicate that: 1) The Hinduism conversion in Southeast Sulawesi has increased every year since the last five years and has occurred in almost all areas of Hindu transmigration, it was dominated by teenagers to adults at various levels of education; 2) There has been a change in values from the social, cultural and spiritual aspects on young Hindu generation in southeast Sulawesi as a result of the Hinduism conversion